I3 High prevalence of huntington's disease in San Marino Republic: an epidemiological survey. (13th September 2016) - Stumpo, Maurizio; Guttmann, Susanna; Volpini, Mirco; Monaldini, Chiara; Manzaroli, Dario; Maffi, Sabrina; Consoli, Federica; Squitieri, Ferdinando
Abstract : Background and rationale: The San Marino Republic is located in the heart of Northern Italy and it is a politically independent small Country: according to census 2013, San Marino's population counts 31.448 inhabitants. As an independent Country, its Government has implemented its own health care system which allows the General Hospital – the only Hospital in the Country - to access to all the inhabitants' health data, even those managed by single territorial health structures. Methods: Because San Marino Republic health organisation is completely independent from Italy, any single person affected by Huntington's and other rare diseases is assisted by the General Hospital's neurologists. This is the reason why we can easily count how many people are affected with Huntington's disease (HD) and start to carefully retrieve all ancestries and genealogical data to link pedigrees for epidemiological purposes. Results: We have so far identified 7, apparently unrelated families, with a total of 10 affected subjects, 19 with 50% risk, 18 with 25% risk and at two more relatives suspected to manifest first symptoms. Such data confirm an impressive frequency of HD in this restricted area with a preliminary estimation of 10/31.448 people (i.e. prevalence of 31.7/100.000 people), representing the highest prevalence esteem in Europe. Conclusion: Thanks to such preliminary epidemiological analysis, San Marino's Government promoted professionals' training in the attempt to provide a correct patients' standard of care, including patients' monitoring, therapeutic initiatives and molecular genetics procedures for predictive testing and confirmation of clinical diagnosis.